PERAN RUSSIAN MANICURE DALAM MENINGKATKAN ESTETIKA NAIL ART : STUDI LITERATUR - Yuanita Saraswati Yuwono; Ivana Alicea Hanandita; Sunarti Sunarti; Wina; Eny Widhia Agustin; Mia Hafizah Tumangger (STKIP Subang, 2026)
Russian manicure is a modern nail care technique that uses specialized electric tools (e-file) to clean the cuticle area in detail and create a neat, aesthetic nail appearance. This study aims to analyze the role of Russian manicure in improving nail art aesthetics through a Systematic Literature Review (SLR). Literature sources were obtained from Google Scholar, Scopus, and PubMed published between 2020–2025. The results show that Russian manicure improves nail cleanliness, enhances the precision of nail art application, and produces a more professional and long-lasting appearance. However, this technique requires proper skills and hygiene standards to avoid irritation or nail damage. Therefore, Russian manicure plays an important role in supporting modern nail art aesthetics.